Voor een gewestelijke bouwarcheologie - Paulo Charruadas; Stéphane Demeter (Brussels Studies, 2011)
Although the situation in Brussels has improved considerably in recent years, the management – identification, protection and preservation – of built heritage from the Old Regime is still faced with a certain number of administrative, regulatory and scientific problems. This article intends to illustrate the importance of the development of regional building archaeology: [1] by reviewing the current situation of the study and protection of historic architectural heritage in Brussels; [2] by identifying the main problems which hinder this management; and [3] by proposing several ideas for solutions and by showing the potential of this type of development for the future of the city‑Region.